Cell loss recovery using interleaved convolutional code for ATM networks - Wong, Kin-Yew; Takahashi, K. (2000)
A cell loss recovery scheme is proposed that uses an interleaved burst-error-correcting convolutional code (thr Berlekamp-Preparata (BP) code) at the convergence sublayer (CS) of a type 1 ATM adaptation layer (AAL). Analysis shows that the overall delay can be reduced by using the new scheme.